Computer aided design of architecture of degradable tissue engineering scaffolds. Issue 15 (18th November 2017) - Heljak, M. K.; Kurzydlowski, K. J.; Swieszkowski, W.
Abstract: One important factor affecting the process of tissue regeneration is scaffold stiffness loss, which should be properly balanced with the rate of tissue regeneration. The aim of the research reported here was to develop a computer tool for designing the architecture of biodegradable scaffolds fabricated by melt-dissolution deposition systems (e.g. Fused Deposition Modeling) to provide the required scaffold stiffness at each stage of degradation/regeneration. The original idea presented in the paper is that the stiffness of a tissue engineering scaffold can be controlled during degradation by means of a proper selection of the diameter of the constituent fibers and the distances between them. This idea is based on the size-effect on degradation of aliphatic polyesters. The presented computer tool combines a genetic algorithm and a diffusion-reaction model of polymer hydrolytic degradation. In particular, we show how to design the architecture of scaffolds made of poly(DL-lactide-co-glycolide) with the required Young's modulus change during hydrolytic degradation.